Poetic Discourse in Péter Esterházy's Novels - Rudaš, Jutka (Anali PAZU HD, 2022)
This paper discloses the principal elements of the poetic discourse in Péter Esterházy's works. Esterházy's entire poetics is based on intertextuality as a special literary strategy, as well as on metaphorical reference in which the reality itself is in a way potentially fictitious and fantastic. Esterházy's works are imbued with breakthrough dimensions of intertextuality, in which every text is caught, where the border between the intra-textual and the extra-textual is blurred, and where quotations, references, various cultural languages and socio-cultural elements intertwine. In the labyrinth of fragments of the quotations, auto- referenciality and literary allusions that Esterházy continuously uses page after page, this paper aims at providing an inside into the complicated net of ruptures and transitions in his novels.
Keywords: intertextuality; referenciality; fiction; Culture Code; allusion